Poetyckie reminiscencje Klemensa Janickiego z podróży do Italii - Miazek-Męczyńska, Monika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
The text focuses on the reminiscences of Clemens Ianitius from his journey to Padova (Italy), where the Polish poet spent two years (1538–40) studying at the University of Padova. In his poetry (especially in his elegies) one can find many remarks connected with Italy described by Ianicius as his intellectual native country.